ANALISIS STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN DAYA SAING PADA PERUSAHAAN SUSI AIR DI MEDAN - Fajar Sardi Syahputra; Fivi Rahmatus Sofiyah (Universitas Sumatera Utara, 2013)
Abstract This research aims to identify and analyze the marketing strategy of Susi Air in Medan by using the SWOT analysis consisting of Strength, Weakness, Opportunities and Threats as a strategy to improve the competitiveness of Susi Air in Medan. This research is a descriptive research using matrix analysis IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), IE (Internal-External, SPACE (Strategy Position and Action Evaluation) and the SWOT Matrix. To obtain the accurate data, the methods used are interviews (in-depth interviews), and test of methods triangulation. Several alternative strategies will be selected using QSP Matrix. The result of this research indicates that Susi Air has considerable strengths and opportunities in the competition, but Susi Air Medan needs to improve its diversification strategy to get more customers. One of the strategies that can be applied by the company is to increase promotional activity both in print and electronic media. Keywords:Competitiveness, Strengths, Weaknesses, Opportunities, Threats